Teacher professional development: study leave criteria as a barrier to qualification upgrading for public primary school teachers in Tanzania - Mbunda, Agustino; Nzima, Ibrahimu; Kimaro, Aurelia (Papers in Education and Development, 2024)
This study examined the barriers to teacher professional development (TPD) arising from study leave criteria for public primary school teachers seeking qualification upgrades in Tanzania. The study employed a qualitative research approach and multiple-case design and was conducted in Kondoa and Chemba districts. 12 Head Teachers (HTs), 2 District Education Officers (DEOs), and 36 teachers were involved. Data were collected through interviews and focus group discussions and analysed thematically. The findings indicated that DEOs and HTs used criteria that acted as barriers to TPD because of increasing restrictions in granting study leave. Such criteria include number of teachers available in schools, self-sponsorship, job experience, nature of the course, teachers' educational levels and readiness for TPD. The study concludes that most study leave criteria contradicted the Government Standing Order for Public Service 2009 and National Framework for Continuous Professional Development of Teachers 2020. The study recommends training for HTs and DEOs regarding TPD guidelines.